Keteladanan Tokoh dalam Serial Animasi Nussa Official - Maisal Jannah (Jurnal Peurawi: Media Kajian Komunikasi Islam, 2020)
This study aims to see the da'wah messages contained in the animated series Nussa and see the exemplary characters. To achieve this goal, the researcher uses qualitative research methods. The data analysis technique used content analysis. The data technique used is through observation, documentation and literature study. Furthermore, the sampling technique used simple random sampling (simple random sampling). The results showed that the animation of Nussa and Rarra is an Islamic animation that conveys the messages of da'wah bil hal, oral bill, and qudwah bill with the values of aqidah, sharia, and morals. The exemplary characters in the animated series Nussa and Rarra match the characters whose messages and messages are conveyed. Almost every episode that the researcher uses as a sample shows the character of a character who deserves to be an example for the audience. In addition to the messages conveyed by displaying Islamic values, morals, and other lessons, the animated series is packaged in a unique and funny way.